1866 Utah Acts 54, ch. 22, tit. 4, § 48 - (:unkn) unknown (My University, 1865)
If such offender, at the time of committing such burglary, is armed with a dangerous weapon, or so arm himself after having entered such dwelling house, or actually assault any person being lawfully therein; or have any confederates present aiding and abetting in such burglary, he shall be punished by imprisonment for life, or any term of years."
Keywords: COMMITTING CRIME W/ WEAPON